Symptom profiles of late‐life anxiety and depression: The influence of migration, religion and loneliness. Issue 9 (3rd April 2019) - Curran, Emma; Rosato, Michael; Cooper, Janine; Mc Garrigle, Christine A.; Leavey, Gerard
Abstract: Objective: To examine (1) clinically relevant anxiety with comorbid depression in an older population, and the presentation of subthreshold symptoms; (2) to assess anxiety and levels of comorbid depression associated with migration, religion, loneliness and long‐term illness. Methods: Analysis of Wave 1 of The Irish Longitudinal Study on Ageing (TILDA) (2009‐2011). Latent class analysis (LCA) was used to define indicative diagnoses of anxiety and depression. We then assessed associations between sociodemographic and socioeconomic factors, past migration, religious practice, social network, loneliness and long‐term illness. Results: For those with clinically relevant anxiety, LCA derived three classes of self‐reported depression: low, subthreshold and high. Approximately 19% were comorbid, and a further 37% reported subthreshold depression. Compared to those with low/no symptoms of depression, those classed as comorbid were more likely to be male, had lower education levels, had spent more time abroad, lower religious attendance, a limited social network, were lonelier and had a long‐term life‐limiting illness. Those with subthreshold levels of depression reported a more restricted social network and more moderate levels of loneliness. Conclusion: Findings support the actuality of comorbidity of both disorders. Consequently, government health strategy on detecting and managing social engagement, loneliness, and psychological disorders in older people may require a more granulated approach.